Cellular Senescence and Ageing: Mechanisms and Interventions - Mylonas, Andreas; O’Loghlen, Ana (Frontiers in Aging, 2022)
The influence of the activation of a cellular phenotype termed senescence and it’s importance in ageing and age-related diseases is becoming more and more evident. In fact, there is a huge effort to tackle these diseases via therapeutic drugs targeting senescent cells named senolytics. However, a clearer understanding of how senescence is activated and the influence it has on specific cellular types and tissues is needed. Here, we describe general triggers and characteristics of senescence. In addition, we describe the influence of senescent cells in ageing and different age-related diseases.